Applications of PET in Diagnosis and Prognosis of Leukemia. (1st September 2020) - Zhao, Zixuan; Hu, Yanwen; Li, Jihui; Zhou, Yeye; Zhang, Bin; Deng, Shengming
As a malignant hematopoietic stem cell disease, leukemia remains life-threatening due to its increasing incidence rate and mortality rate. Therefore, its early diagnosis and treatment play a very important role. In the present work, we systematically reviewed the current applications and future directions of positron emission tomography (PET) in patients with leukemia, especially 18 F-FDG PET/CT. As a useful imaging approach, PET significantly contributes to the diagnosis and treatment of different types of leukemia, especially in the evaluation of extramedullary infiltration, monitoring of leukemia relapse, detection of Richter's transformation (RT), and assessment of the inflammatory activity associated with acute graft versus host disease. Future investigations should be focused on the potential of PET/CT in the prediction of clinical outcomes in patients with leukemia and the utility of novel radiotracers.